Mi‘rāj al-Sālikīn ilá Martabat al-Wāṣilīn bi Jāh Sayyid al-‘Ārifīn: Baqā’ al-ṭarīqah al-Shaṭārīyah fī Aceh fatrat al-isti‘mār - Hermansyah, Hermansyah (Studia Islamika, 2013)
This article discusses the development of Syattariyah Sufi order as one of religious traditions in Aceh in the colonial era based on the manuscript of Muhammad Khatib Langien’s Mi‘rāj al-Sālikīn ilá Martabat al-Wāsilīn bi-Jāh Sayyid al-Mursalīn. The Syattariyah teachings in Mi‘rāj al-Sālikīn have proved the existence of Muhammad Khatib Langien in the Malay-archipelago world. In applying his teachings, Muhammad Khatib Langien has the different procedures than that one of  ‘Abd al-Raūf al-Fansuri. In addition to practical teachings, Muhammad Khatib Langien employs local symbols such as wearing skullcaps and turbans in the swear oath (bay‘ah) process. This tradition is meant to respond the foreign culture as well as to show the identity of each members of Syattariyah sufi order. It is proved that Muhammad Khatib Langien’s teachings that can be accepted by all people and groups even without having support from the local authorities at the time.DOI: 10.15408/sdi.v20i3.515